Welfare and spatial distribution of noise levels in swine nursery - Flavio A. Damasceno; Carlos E. A. Oliveira; Gabriel A. e S. Ferraz; João A. C. do Nascimento; Jairo A. O. Saraz; Leidimar F. Brandão (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The aim of this study was to evaluate the welfare and spatial distribution of noise levels in a swine nursery during the first three weeks of animal’s life. The climatic conditions were evaluated through the dry-bulb temperature (Tdb), relative humidity (RH) and black globe temperature and humidity index (BGHI) and allowed us to observe that the heating system influenced the conditions in the environment, and the use of the air conditioning system did not guarantee animal’s comfort conditions. The analysis on the spatial distribution of noise levels was performed using geostatistics and demonstrated the occurrence of spatial variability inside the facilities. The highest frequencies of noise levels were concentrated between 60 and 70 dB, and the highest noise values were observed near the fans. The mean BGHI values were below the thermal comfort range for piglets in all systems tested.